Boosting non-state climate action in the European Union - Sander Chan; Jacopo Bencini (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The 2015 Paris Agreement and the accompanying Paris Decision recognise the importance of climate actions by non-state actors, such as businesses, civil society organisa¬tions, cities, regions and cooperative initiatives, to reduce greenhouse gases (GHG) and to adapt to climate change as necessary complements to governmental commitments. Prominent international platforms, such as the Non-State Actor Zone for Climate Action (NAZCA) by the Secretariat of the United Nations Framework Convention on Climate Change (UNFCCC) and the Climate Initiatives Platform ad¬min-istered by the United Nations Environmental Pro¬gramme/Technical University of Denmark (UNEP/DTU) Part¬ner¬ship, have greatly improved the visibility of such actions. Within this dynamic field of non-state climate action, non-state actors based in the European Union (EU) can be considered global leaders. Actions led by EU-based actors represent most initiatives registered with UNFCCC's NAZCA platform. Moreover, individual member states have played leading roles in the Global Climate Action Agenda (also known as the Marrakech Partnership for Global Climate Action). A recent study by the European Economic and Social Committee (EESC) and the German Develop¬ment Institute / Deutsches Institut für Entwick¬lungs¬politk (DIE) moreover finds that actions led by EU-based non-state actors are performing well compared with the global average (EESC, 2018). However, the implementation of non-state actions is not evenly distributed. In absolute terms, existing initiatives in Central and Eastern Europe (CEE) are underrepresented. Moreover, few actions led by EU-based non-state actors are recorded in international platforms in areas such as forestry, transport and construction (EESC, 2018). The need for more, and more effective, non-state actions is evident given the fact that current EU climate policies are inconsistent with the goals of the Paris Agreement. According to the Climate Action Tracker, the EU's Nationally Determined Contribution (NDC) is insufficient; if all govern¬ments had targets similar to the EU, global warming could exceed 2°C and possibly even 3°C. Non-state actors could make important additional mitiga¬tion and adaptation contributions, both directly, for example, through new installations, as well as indirectly, for example, by encouraging behavioural change. Moreover, they could inspire governments and the EU to be more ambi¬tious. However, currently non-state actions are not easy to track. Despite a strong focus on climate mitigation, most actions led by EU-based actors do not set clear GHG reduction targets. In addition, many relevant actions remain unrecorded. This paper explores what is necessary to accelerate non-state actions and enhance their effectiveness in the EU and as a solution suggests that a light-touch framework be implemented to stimulate bottom-up climate actions. This framework should respond to the needs and challenges experienced by a range of stakeholders while building on existing efforts. Moreover, a well-designed framework could help address the imbalances identified in this study.
Keywords: 330; Klimawandel